Pembuatan Website Desa Wisata Sebagai Media Promosi Potensi Wisata di Desa Sebatu - Kanha, I Gusti Ngurah; Wijaya, I Nyoman Yudi Anggara; Putra, I Gede Juliana Eka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Information technology has become an important element in everyday life, including in the tourism sector. Tourism is one sector that can be relied on to improve a country's economy. Indonesia, with its natural wealth and cultural diversity, has great potential in the tourism industry. Sebatu Village, located in Tegalalang District, Gianyar Regency, Bali, has various tourism potentials that are not yet fully known by tourists due to limited information. To overcome this problem, a special website was developed to promote the tourism potential of Sebatu Village. This website aims to serve as promotional media and an organized information center, enabling the delivery of structured and clear information. It is hoped that this website can increase tourist interest in visiting and make Sebatu Village a more recognized and sustainable tourist destination. Methods for implementing this activity include interviews and analysis, collecting Sebatu Village tourism data, creating a website, creating a book and video guide for website management, website management training, and evaluation via questionnaires to assess the effectiveness of the training for IT staff. Community service in Sebatu Village has succeeded in providing effective promotional media, making it easier for tourists to access information, and increasing the competence of Sebatu Tourism Village IT staff in efficiently managing the website.